WORK MOTIVATION, WORK DISCIPLINE, EMPLOYEE PERFORMANCE, AND ORGANIZATIONAL CULTURE FROM REGIONAL INSPECTORATE OF ANAMBAS ISLAND REGENCY - Risdayani, Risdayani -; Rino, Rino (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2024)
The main factor supporting the success of an organization is human resources who have work motivation, work discipline, and good performance to form an organizational culture. The purpose of this study is to see the influence and relationship between work motivation, work discipline, employee performance and organizational culture. The approach of this study is quantitative with a comparative method. This study was conducted at the Regional Inspectorate Anambas Island Regency for 4 months. The participants of this study were all 85 employees of the inspectorate office. Data collection used a questionnaire and data analysis techniques used the Independent-sample t-test. From the results of the study, it can be concluded that work motivation has a significant effect on organizational culture, work discipline has a significant effect on organizational culture, employee performance has a significant effect on organizational culture, work motivation has a significant effect on work discipline, work discipline does not have a significant effect on employee performance, and work motivation has a significant effect on employee performance. The limitations of this study lie in the method used, which only uses quantitative methods. Recommendations for further researchers are to be able to study more deeply about this topic by combining quantitative and qualitative methods. Further researchers can also examine the influence or relationship of other aspects in an organization, such as organizational effectiveness, organizational performance, employee competence, reward systems and other factors that influence the success of an organization.